(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Despite the large number of works devoted to the influence of the ecological situation in the Aral Sea region on public health, insufficient attention is paid to the study of the influence of environmental factors on the organ of vision. Purpose: to analyze the detection and condition of some eye diseases in the Aral Sea population. Material and methods. The data of statistical reports of medical institutions for 2009-2019 is analyzed. Results. Over the past 11 years, among the population of the Republic of Karakalpakstan, the total and primary incidence of eyes and its appendages increased by 39% and 68.5%, respectively. The overall incidence of cataracts in the period from 2009 to 2011 tended to decrease by 16.4% (from 161.05 to 138.27), and the primary incidence by 50%. But from 2012 to 2019, these indicators have dynamically increased by 26% and 89%, respectively. The general and primary incidence with glaucoma and myopia has not had significant dynamics over the past 11 years. However, the general and primary morbidity with myopia is 1.22 and 1.36 times higher (p≥0.01), respectively, than the Republic of Uzbekistan as a whole. Conclusion. The general and primary incidence of the eyes and its appendages in the Aral Sea region has a tendency to increase every year. At the same time, the dynamics of the increase in the incidence falls on the share of patients with conjunctival diseases, myopia and cataracts. The average results of the incidence of cataracts and myopia in the Aral Sea region are significantly greater than in the Republic of Uzbekistan as a whole. Perhaps this is due to increased pollution of the atmosphere of the region and disease resistance to traditional methods of treatment and prevention of these ophthalmopathologies.